Antioxidant Property and Health Benefits of Grape Byproducts - Bhise, Suresh; Kaur, A; Gandhi, Neeraj; Gupta , Rahul (Journal of Postharvest Technology, 2024)
Grape skin and seeds, produced by the winemaking industry, are increasingly used to obtain functional food ingredients. Grape seed is a better source of antioxidative constituents than skins of grape/wine byproducts. Functional ingredients of grape seed include several flavonoids with a phenolic nature such as monomeric flavanols, dimeric, trimeric, and polymeric procyanidins, and phenolic acids. The antioxidant activity of grape seed phenolic compounds is closely associated with activity against various types of cancer as well as cardiovascular and other dermal disorders. Grape seed has antioxidant, antiallergenic, antihistamine, anti-inflammatory and immune boosting properties and it helps the body against allergens and carcinogens. Grape seed extract is frequently recommended to combat macular degeneration, cataracts, and eyestrain. The present review article discusses the functional characteristics of grape pomace and their health benefits against several human diseases and disorders.